Kuzmenko A.G. Way of friction as a base concept and description at slipping of contacting surfaces. - Кузьменко, А.Г. (Problems of Tribology, 2014)
Given determination of way of friction for the case of tribosystem of two contacting surfaces for a case, when one of surfaces is mobile, other is immobile. Procedure of determination and essence of sizes of way of friction is rotined on the example of discrete contact mikroburries and on the example of contact of continuous surfaces. The examples of practical determination are resulted by a friction for the different pair of friction. It is rotined that effects of different wear of pair of friction in it is possible to explain the different coefficients of the mutual ceiling by the different ways of friction for contacting surfaces. It is rotined that the effect of influence of direct or reverse pair on a wear is also explained different in size ways of friction in one and by a friend cases.